Nonhuman Primate Models in Biomedical Research: State of the Science and Future Needs - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Nonhuman primates represent a small fraction of animals used in biomedical research, but they remain important research models due to their similarities to humans with respect to genetic makeup, anatomy, physiology, and behavior. Limitations in the availability of nonhuman primates have been exacerbated by the COVID-19 pandemic and recent restrictions on their exportation and transportation, impacting National Institutes of Health (NIH)-funded research necessary for both public health and national security. Additionally, there is continued interest in understanding whether and how nonanimal models can be used to answer scientific questions for which nonhuman primates are currently used. At the direction of the U.S. Congress, NIH asked the National Academies of Sciences, Engineering, and Medicine to convene an expert committee to conduct a landscape analysis of current and future use of nonhuman primates in NIH-supported biomedical research, as well as opportunities for new approach methodologies to complement or reduce reliance on nonhuman primate models. This report provides the committee findings and conclusions.
Keywords: Biology and Life Sciences; Health and Medicine

Health Systems Science Education: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
The National Academies Global Forum on Innovations in Health Professional Education held a public workshop in November 2023. Speakers explored how health professional educators and providers with health systems science (HSS) training can prepare learners to work together within health systems, resulting in better patient care, improved population health, and enhanced health professional well-being. Organizers hosted a public pre-workshop in October 2023 to create a foundational understanding of HSS prior to their workshop.
Keywords: Education; Health and Medicine

Report Series: Committee on Biological and Physical Sciences in Space: Using Commercial Lunar Payload Services (CLPS) to Achieve Lunar Biological and Physical Science Objectives: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
After several decades since the last human visit, NASA is planning to return to the Moon, this time not only to visit but also to carry out extensive scientific experiments, establish a habitat occupied by astronauts, and learn lessons that will help in preparations for the eventual establishment of a human presence on Mars. The Commercial Lunar Payload Services (CLPS) program, overseen by NASA, will provide transport to the Moon for scientists who want to carry out research on the lunar surface or in orbit around the Moon. Recognizing the need to introduce and explain the CLPS program to researchers, the Committee on Biological and Physical Sciences in Space of the National Academies of Sciences, Engineering, and Medicine held a workshop on March 24-25, 2021 entitled "Using Commercial Lunar Payload Services (CLPS) to Achieve Lunar Biological and Physical Science Objectives". The organization of the workshop was guided by the following question: Looking at the period of time prior to the release of the next decadal survey, how can this community support and utilize CLPS to address areas of research? This workshop proceedings summarizes the presentations and discussions from the workshop sessions.
Keywords: Space and Aeronautics

Advancing Chemistry and Quantum Information Science: An Assessment of Research Opportunities at the Interface of Chemistry and Quantum Information Science in the United States - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The field of quantum information science (QIS) has witnessed a dramatic rise in scientific research activities in the 21st century as excitement has grown about its potential to revolutionize communications and computing, strengthen encryption, and enhance quantum sensing, among other applications. While, historically, QIS research has been dominated by the field of physics and computer engineering, this report explores how chemistry - in particular the use of molecular qubits - could advance QIS. In turn, researchers are also examining how QIS could be used to solve problems in chemistry, for example, to facilitate new drug and material designs, health and environmental monitoring tools, and more sustainable energy production. Recognizing that QIS could be a disruptive technology with the potential to create groundbreaking products and new industries, Advancing Chemistry and Quantum Information Science calls for U.S. leadership to build a robust enterprise to facilitate and support research at the intersection of chemistry and QIS. This report identifies three key research areas: design and synthesis of molecular qubit systems, measurement and control of molecular quantum systems, and experimental and computational approaches for scaling qubit design and function. Advancing Chemistry and Quantum Information Science recommends that the Department of Energy, National Science Foundation, and other funding agencies should support multidisciplinary and collaborative research in QIS, the development of new instrumentation, and facilities, centralized and open-access databases, and efforts to create a more diverse and inclusive chemical workforce.
Keywords: Math, Chemistry, and Physics

Assessment of Commercial Space Platforms for Earth Science Instruments: Report Series—Committee on Earth Science and Applications from Space - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Space-based Earth observations enable global observations of the land surface, biosphere, solid Earth, atmosphere, cryosphere, and oceans. Earth observations from space, combined with data acquired from in situ and ground-based instruments, help scientists understand the components of the Earth system and their interactions and enable wide-ranging applications, including forecasts of weather and air quality, projections of future climate, management of natural resources, ecological forecasting, disaster management, drought and wildfire prediction, and the mapping and prediction of vector borne/animal diseases. At the request of NASA Earth Science Division, this report assesses the potential use of a proposed multi-user, robot-tended, uncrewed commercial space platform as a potential host for a large number of Earth remote sensing instruments. Assessment of Commercial Space Platforms for Earth Science Instruments evaluates the utility and practicality of a platform in a Sun-synchronous orbit, capable of hosting 20 or more instruments.
Keywords: Space and Aeronautics

Rise and Thrive with Science: Teaching PK-5 Science and Engineering - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Research shows that that children learn science and engineering subjects best by engaging from an early age in the kinds of practices used by real scientists and engineers. By doing science and engineering, children not only develop and refine their understanding of the core ideas and crosscutting concepts of these disciplines, but can also be empowered to use their growing understanding to make sense of questions and problems relevant to them. This approach can make learning more meaningful, equitable, and lasting. Using cases and shorter examples, Rise and Thrive with Science shows what high-quality teaching and learning in science and engineering can look like for preschool and elementary school children. Through analyses of these examples and summaries of research findings, the guide points out the key elements of a coherent, research-grounded approach to teaching and learning in science and engineering. This guide also discusses the kinds of support that educators need to implement effective and equitable instruction for all children. This book will provide inspiration for practitioners at the preschool and elementary levels to try new strategies for science and engineering education, whatever their level of experience. Rise and Thrive with Science will be an essential guide for teachers as they organize instruction to enable young children to carry out their own science investigations and engineering design projects, determine the kinds of instruction that lead to meaningful learning, and try to engage every one of their students.
Keywords: Education

Toward a Future of Environmental Health Sciences: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
What could the future of environmental health sciences hold, and what steps might be taken now to guide the field's trajectory? To envision a future research enterprise that integrates environmental health sciences, biomedical science, prevention research, and disease-specific research across the continuum from fundamental discovery research through the application of this research to population health, the National Academies of Sciences, Engineering, and Medicine hosted a workshop titled Towards a Future of Environmental Health Sciences on April 26-27, 2022. This publication summarizes the presentations and discussion of the workshop.
Keywords: Environment and Environmental Studies

Ontologies in the Behavioral Sciences: Accelerating Research and the Spread of Knowledge - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
New research in psychology, neuroscience, cognitive science, and other fields is published every day, but the gap between what is known and the capacity to act on that knowledge has never been larger. Scholars and nonscholars alike face the problem of how to organize knowledge and to integrate new observations with what is already known. Ontologies - formal, explicit specifications of the meaning of the concepts and entities that scientists study - provide a way to address these and other challenges, and thus to accelerate progress in behavioral research and its application. Ontologies help researchers precisely define behavioral phenomena and how they relate to each other and reliably classify them. They help researchers identify the inconsistent use of definitions, labels, and measures and provide the basis for sharing knowledge across diverse approaches and methodologies. Although ontologies are an ancient idea, modern researchers rely on them to codify research terms and findings in computer-readable formats and work with large datasets and computer-based analytic techniques. Ontologies in the Behavioral Sciences: Accelerating Research and the Spread of Knowledge describes how ontologies support science and its application to real-world problems. This report details how ontologies function, how they can be engineered to better support the behavioral sciences, and the resources needed to sustain their development and use to help ensure the maximum benefit from investment in behavioral science research.
Keywords: Behavioral and Social Sciences

Roots and Trajectories of Violent Extremism and Terrorism: A Cooperative Program of the U.S. National Academy of Sciences and the Russian Academy of Sciences (1995-2020) - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
During the past 25 years, the U.S. National Academies of Sciences, Engineering, and Medicine, in collaboration with the Russian Academy of Sciences, have carried out a wide variety of activities to improve understanding of the challenges in containing and reducing ethnic conflicts, violent extremism, and terrorism. Roots and Trajectories of Violent Extremism and Terrorism provides an overview of this cross-ocean program, which has involved American and Russian scientists, engineers, and medical professionals from a large number of government agencies, leading research institutions, think tanks, educational institutions, analytical centers, and consulting and commercial firms in the two countries. This report highlights challenges addressed by the academies over many years that remain of current interest as the U.S., Russian, and other governments continue to cope with old and new forms of aggression that threaten the livelihood of populations at home and abroad.
Keywords: Conflict and Security Issues

The Arctic in the Anthropocene: Emerging Research Questions - National Research Council (The National Academies Press, 2014)
Once ice-bound, difficult to access, and largely ignored by the rest of the world, the Arctic is now front and center in the midst of many important questions facing the world today. Our daily weather, what we eat, and coastal flooding are all interconnected with the future of the Arctic. The year 2012 was an astounding year for Arctic change. The summer sea ice volume smashed previous records, losing approximately 75 percent of its value since 1980 and half of its areal coverage. Multiple records were also broken when 97 percent of Greenland's surface experienced melt conditions in 2012, the largest melt extent in the satellite era. Receding ice caps in Arctic Canada are now exposing land surfaces that have been continuously ice covered for more than 40,000 years. What happens in the Arctic has far-reaching implications around the world. Loss of snow and ice exacerbates climate change and is the largest contributor to expected global sea level rise during the next century. Ten percent of the world's fish catches comes from Arctic and sub-Arctic waters. The U.S. Geological Survey estimated that up to 13 percent of the world's remaining oil reserves are in the Arctic. The geologic history of the Arctic may hold vital clues about massive volcanic eruptions and the consequent release of massive amount of coal fly ash that is thought to have caused mass extinctions in the distant past. How will these changes affect the rest of Earth? What research should we invest in to best understand this previously hidden land, manage impacts of change on Arctic communities, and cooperate with researchers from other nations? The Arctic in the Anthropocene reviews research questions previously identified by Arctic researchers, and then highlights the new questions that have emerged in the wake of and expectation of further rapid Arctic change, as well as new capabilities to address them. This report is meant to guide future directions in U.S. Arctic research so that research is targeted on critical scientific and societal questions and conducted as effectively as possible. The Arctic in the Anthropocene identifies both a disciplinary and a cross-cutting research strategy for the next 10 to 20 years, and evaluates infrastructure needs and collaboration opportunities. The climate, biology, and society in the Arctic are changing in rapid, complex, and interactive ways. Understanding the Arctic system has never been more critical; thus, Arctic research has never been more important. This report will be a resource for institutions, funders, policy makers, and students. Written in an engaging style, The Arctic in the Anthropocene paints a picture of one of the last unknown places on this planet, and communicates the excitement and importance of the discoveries and challenges that lie ahead.
Keywords: Earth Sciences; Environment and Environmental Studies

Emerging Technologies for Construction Delivery - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
The uses and levels of maturity of five advanced technology areas visualization and modeling, interconnected technologies, safety technologies, instrumentation and sensors, and unmanned aircraft systems in transportation highway construction projects are documented in TRB’s National Cooperative Highway Research Program (NCHRP) Synthesis 534: Emerging Technologies for Construction Delivery. The synthesis also investigates the implementation barriers and success factors for these technology areas and discusses the lessons learned as noted by state DOTs in their effort to study, test, and implement a new construction technology.As the highway construction industry infuses more technologies into the process of project delivery, state DOTs have an opportunity to realize improved project performance regarding cost, schedule, and quality.The Federal Highway Administration (FHWA) Every Day Counts (EDC) initiatives promote the use of various advanced and emerging technologies (e.g., automated machine guidance, unmanned aircraft systems, building information modeling, handheld instruments and devices, and work zone intrusion detection systems).
Keywords: Transportation and Infrastructure

Science Diplomacy to Promote and Strengthen Basic Research and International Cooperation: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The Global Research Council (GRC) brings together heads of science and engineering funding agencies from around the world to promote data sharing and best practices, and to support high-quality collaboration. The GRC plays an important role in science diplomacy, namely by promoting and strengthening basic research and international collaboration. To further define the broader role of the GRC in this space and to identify opportunities to advance science diplomacy, the National Academies of Sciences, Engineering, and Medicine convened a virtual workshop on March 12, 15, and 16, 2021. Participants explored ways in which science diplomacy can promote basic research; addressed challenges to science diplomacy; and considered future opportunities to advance science diplomacy. This Proceedings of a Workshop-in Brief provides a high-level summary of the workshop discussion.
Keywords: Policy for Science and Technology

Taking Stock of Science Standards Implementation: Planning for Progress: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
It has been just over ten years since the release of the Framework on K-12 Science Education and the Next Generation Science Standards. As states continue their implementation efforts of state standards, there is a need for a reflection on these efforts looking at curriculum, instruction, assessment, professional learning, and policy. To identify the conditions and develop a road map for moving implementation efforts forward, the National Academies of Sciences, Engineering, and Medicine held a hybrid summit on April 26 and 27, 2022. Participants shared ideas to imagine what science education could look like in ten years, and how these visions might be achieved. This publication summarizes the presentation and discussion or the event.
Keywords: Education

Foundations of Data Science for Students in Grades K-12: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
On September 13 and 14, 2022, the Board on Science Education at the National Academies of Sciences, Engineering, and Medicine held a workshop entitled Foundations of Data Science for Students in Grades K–12. Speakers and participants explored the rapidly growing field of K-12 data science education, by surveying the current landscape, surfacing what is known, and identifying what is needed to support student learning, develop curriculum and tools, and prepare educators. To support these conversations, four papers were commissioned and discussed during the workshop. This publication summarizes the presentations and discussion of the workshop.
Keywords: Education

Climate Intervention in an Earth Systems Science Framework: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
To consider how an Earth system science approach can inform research on climate intervention, The National Academies of Sciences, Engineering, and Medicine held a virtual workshop on June 20-22, 2023 titled Climate Intervention in an Earth Systems Science Framework. Individuals with a wide range of physical, ecological, and social sciences expertise explored climate interventions within the context of convergent research and the capacities of the National Science Foundation (NSF). The workshop drew on the National Academies report Next Generation Earth Systems Science at the National Science Foundation, which called upon NSF to pursue an Earth systems science initiative that emphasizes research on interconnections and feedback between natural and social processes; focuses on real-world problems; enhances the participation of social, engineering, and data scientists; and strengthens efforts to include diverse perspectives in research.
Keywords: Environment and Environmental Studies; Earth Sciences

The Science of Implicit Bias: Implications for Law and Policy: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
On March 22-23, 2021, an ad hoc planning committee under the auspices of the National Academies of Sciences, Engineering, and Medicine's Committee on Science, Technology, and Law hosted a virtual workshop titled The Science of Implicit Bias: Implications for Law and Policy. Implicit bias has been commonly defined as any unconscious or unacknowledged preferences that can affect a person's beliefs or behaviors, and in particular, an unconscious favoritism toward or prejudice against people of a certain race, gender, or group that influences one's own actions or perceptions. The methods for identifying the presence and degree of an individual's implicit bias, the presence of implicit bias throughout society, and the successes or failures of attempts to mitigate implicit bias are topics of much scientific inquiry, with ramifications for law and policy as well as a multitude of organizational settings. The ways in which implicit bias reflects or contributes to structural and systemic racism in the U.S. remains an open and urgent question. The workshop, organized by the Committee on the Science of Implicit Bias: Implications for Law and Policy, was convened to better understand the state of the science on this topic in the context of critical and ongoing discussions about racism in the United States. racism in the U.S. Funding for the workshop was provided by the Ford Foundation.
Keywords: Behavioral and Social Sciences; Policy for Science and Technology

Developing a Toolkit for Fostering Open Science Practices: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The National Academies Roundtable on Aligning Incentives for Open Science, established in 2019, has taken on an important role in addressing issues with open science. The roundtable convenes critical stakeholders to discuss the effectiveness of current incentives for adopting open science practices, current barriers of all types, and ways to move forward in order to align reward structures and institutional values. The Roundtable convened a virtual public workshop on fostering open science practices on November 5, 2020. The broad goal of the workshop was to identify paths to growing the nascent coalition of stakeholders committed to reenvisioning credit/reward systems (e.g., academic hiring, tenure and promotion, and grants)to fully incentivize open science practices. The workshop explored the information and resource needs of researchers, research institutions, government agencies, philanthropies, professional societies, and other stakeholders interested in further supporting and implementing open science practices. This publication summarizes the presentations and discussion of the workshop.
Keywords: Policy for Science and Technology

Openness, International Engagement, and the Federally Funded Science and Technology Research Enterprise: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
On November 14 and 15, 2022, the National Academies of Sciences, Engineering, and Medicine convened a two-day workshop under the auspices of the National Science, Technology, and Security Roundtable to assess the state of the U.S. research enterprise in a time of increasing global competition. The workshop also featured discussion of the challenges confronting researchers as they seek to ensure the vitality of research and innovation in America, foster increased international scientific research cooperation, and simultaneously counter illicit foreign interference that threatens national security interests. This publication summarizes the presentation and discussion of the workshop.
Keywords: Policy for Science and Technology

Empowering the Defense Acquisition Workforce to Improve Mission Outcomes Using Data Science - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The effective use of data science - the science and technology of extracting value from data - improves, enhances, and strengthens acquisition decision-making and outcomes. Using data science to support decision making is not new to the defense acquisition community; its use by the acquisition workforce has enabled acquisition and thus defense successes for decades. Still, more consistent and expanded application of data science will continue improving acquisition outcomes, and doing so requires coordinated efforts across the defense acquisition system and its related communities and stakeholders. Central to that effort is the development, growth, and sustainment of data science capabilities across the acquisition workforce. At the request of the Under Secretary of Defense for Acquisition and Sustainment, Empowering the Defense Acquisition Workforce to Improve Mission Outcomes Using Data Science assesses how data science can improve acquisition processes and develops a framework for training and educating the defense acquisition workforce to better exploit the application of data science. This report identifies opportunities where data science can improve acquisition processes, the relevant data science skills and capabilities necessary for the acquisition workforce, and relevant models of data science training and education.
Keywords: Conflict and Security Issues; Computers and Information Technology; Math, Chemistry, and Physics

Evolving the Culture of Science and Training in Neuroscience to Meet a Changing World: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Recent events, including the COVID-19 pandemic and the collective awakening around issues related to racial justice, diversity, and inclusion, have underscored the challenges facing neuroscience and neuroscience training. To address these challenges, the Forum on Neuroscience and Nervous System Disorders of the National Academies of Sciences, Engineering, and Medicine convened a series of virtual workshops on neuroscience training with the goal of reconsidering how we think about neuroscience training in a rapidly changing world. On February 22, 2021, the fifth and final workshop in this series, titled Evolving the Culture of Science and Training in Neuroscience to Meet a Changing World, brought together stakeholders from across the neuroscience ecosystem to discuss how the culture of science and scientific training can become more inclusive, balanced, and adaptive to changing times. This final workshop expanded on many issues raised in previous workshops, including the importance of mental health and well-being in academic research; how to resist the legacy of white supremacy and support diversity in academia; and how to redefine what success means for neuroscientists in both academic and non-academic settings. This publication summarizes the discussions that occurred at the workshop.
Keywords: Health and Medicine